Trichoderma Harzianum WKY1: an indole acetic acid producer for growth improvement and anthracnose disease control in sorghum. Issue 5 (4th May 2017) - Saber, Wesam I. A.; Ghoneem, Khalid M.; Rashad, Younes M.; Al-Askar, Abdulaziz A.
ABSTRACT: The efficiency of two isolates of Trichoderma harzianum (WKY1 and WKY5) as bio-control agents against anthracnose disease in sorghum was investigated. In vitro, T . harzianum WKY1 isolate showed superiority in terms of inhibition of both mycelial growth and spore germination of Colletotrichum sublineolum, the causative agent of sorghum anthracnose, as well as induction of the sorghum seed germination over T . harzianum WKY5 isolate. The culture filtrate of the selected isolate ( T. harzianum WKY1) was analysed using GC-MS system to determine their chemical constituents. Twenty-nine components with varied existence percentages were identified. Although T . harzianum WKY1 produced the phytohormone indole-3-acetic acid (IAA) on tryptophan free medium, a marked dependency on tryptophan for the production of IAA was noticed. Nutritional components were optimized for maximizing IAA production using the central composite design. The optimum levels were 1.06, 29.86 and 2.93 g L −1 from tryptophan, sucrose and NaNO3, respectively, with a maximum IAA biosynthesis (138.9 µg mL −1 ) after five days of incubation. Production of IAA in the culture filtrate of T. harzianum WKY1 was qualitatively and quantitatively analysed by LC-MS system using a reference standard of IAA. Under greenhouse conditions, application of T . harzianum WKY1 and/or its filtrate reduced greatly the disease severity as well as improved the plant growth of sorghum. From the present data, we can recommend the application of T . harzianum WKY1 as a dual purpose bio-agent for biological control of anthracnose disease and plant growth promotion.